Penerapan Metode User Centered Pada User Interface Sicyca Mobile - Muhammad Rizqi Farhandy Akbar; Erwin Sutomo; Endra Rahmawati (Jurnal Sistem Informasi Universitas Dinamika, 2022)
One of the information technology services available at Dinamika University is the Academic Information System or better known as SICYCA (Cyber Campus Information System). Sicyca is an academic information system application that provides student academic information. Sicyca has 2 (two) versions of the application, namely the web version and the Mobile version. Based on the results of a questionnaire involving Dinamika University students, problems were found in the Sicyca Mobile application. Based on the evaluation of the initial design using the User Experience Questionnaire (UEQ), the initial design of the Sicyca Mobile application has an average of 0.05 and is included in the